2020
DOI: 10.1039/d0lc00724b
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic device for TEM sample preparation

Abstract: We present a capillary-driven microfluidic single-use device that prepares a TEM grid with minimal user interaction. The user only initiates the sample preparation process, waits for about one minute and then collects the TEM grid, ready for imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The device was fabricated using lamination technology, as described previously. ,, Individual layers of hydrophilic sheets, adhesive tapes, magnetic tapes, and paper were structured using a laser cutter (VLS 2.30, Universal Laser Systems, Austria). Blood filters were cut into 10 × 10 mm 2 pieces using a scalpel.…”
Section: Methodsmentioning
confidence: 99%
“…The device was fabricated using lamination technology, as described previously. ,, Individual layers of hydrophilic sheets, adhesive tapes, magnetic tapes, and paper were structured using a laser cutter (VLS 2.30, Universal Laser Systems, Austria). Blood filters were cut into 10 × 10 mm 2 pieces using a scalpel.…”
Section: Methodsmentioning
confidence: 99%
“…Using open microfluidic platforms will reduce the dimensions and maintain the general form factor of the microwell plate, thereby minimizing surface exposure and enabling sample recovery through nano-pipetting [ 1 , 25 ]. Other approaches have been developed by contact pin-printing methods in which pipetting robots automatically dispense liquids at the Transmission Electron Microscopy grid, such as a capillary-driven microfluidic single-use device [ 26 ]. These approaches have the advantages of reducing the volumes of the sample as well as providing automation possibilities, while they also have some disadvantages, such as the need for special instrumentation, and representing a significant increase in complexity and being more time consuming than the manual protocol [ 26 ].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Other approaches have been developed by contact pin-printing methods in which pipetting robots automatically dispense liquids at the Transmission Electron Microscopy grid, such as a capillary-driven microfluidic single-use device [ 26 ]. These approaches have the advantages of reducing the volumes of the sample as well as providing automation possibilities, while they also have some disadvantages, such as the need for special instrumentation, and representing a significant increase in complexity and being more time consuming than the manual protocol [ 26 ]. Mukhitov et al suggested a microfluidic device for the preparation of the grids, in which the grid is contained in a microfluidic canal and the liquid for sample preparation is driven by an external pressure pump, thereby improving preparation consistency [ 27 ].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Optimization of specimen preparation using non-radioactive stains Preparation of efficient embedding and even specimen spreading on the grid support is a prerequisite for an unbiased TEM assessment and imaging (Figure 1A) (Hauser et al, 2020). The stain helps to maintain the specimen integrity while ensuring a good contrast (Figure 1B) for biological samples.…”
Section: Tem Workflow For the Analysis Of Vlpsmentioning
confidence: 99%